Active control of wall pressure flow field at low supersonic Mach numbers - Asad Ullah, Mohammed; Bashir, Musavir; Janvekar, Ayub; Khan, Sher Afghan (International Organization of Scientific Research ( IOSR ), 2016)
This paper presents an experimental study of airflow from convergent-divergent nozzles discharged into enlarged duct, focusing attention on the flow development in the duct. To investigate the influence of active control on the flow field developed in the duct, the micro jets of 0.05 mm radius orifice placed at 900 interval along the base at 6.5 mm from the main jet were employed. The Mach number of this study was 1.3. The area ratio of the present study was 2.56. The NPR presented are from 3, 5, 7, 9, and 11 respectively. The L/D ratio of the duct was varied from 10 to 1. The level of expansion at the nozzle exit influences the wall pressure very strongly since in the present case all the NPRs of the tests are under expanded. For all the L/D the entire flow field in the duct is full of waves, the few shock wave is so powerful that the wall pressure is equal to the atmospheric pressure or more. At L/D = 3, it is seen that due to the influence of the back pressure the number of compression and expansion waves have reduced drastically. The flow field with and without control is identical.